Enhancing sustainability in meat production through insect biorefinery - Jee Young Kim; Jonghyun Park; Dong-Jun Lee; Ye-Bin Choi; Youngjun Choi; Won-Kun Park; Bonwoo Koo; Kwanho Park; Doyeon Lee; Eilhann E. Kwon (npj Science of Food)
Abstract Valuable feed crops and fossil fuel energy are used to produce animal meat. To become sustainable, meat production methods must adapt to include non-food substrates and renewable fossil-fuel alternatives. We evaluated the potential of protein livestock feed and biodiesel production through insect biorefining. The bioconversion efficiency of organic waste into black soldier fly larvae (BSFL) biomass was 32.0–35.8% after 24 d. The protein and lipid composition of BSFL changed with the cultivation time. The substrate influenced lipid content, and low lipid content led to lower lipid accumulation in the BSFL. Nevertheless, the potential productivity of proteins (42,471–48,345 kg ha−1 y−1) and lipids (41,642–64,708 kg ha−1 y−1) from BSFL cultivation with organic waste was higher than that of conventional livestock feed/biodiesel feedstocks, such as maize or soybean. In conclusion, insect biorefineries using BSFL can contribute significantly to the establishment of sustainable meat production.